PENGARUH FINANCIAL DISTRESS DAN DIVIDEND PAYOUT RATIO TERHADAP PERUBAHAN HARGA SAHAM - Ririanty, Reffida Octian; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the Financial Distress and Dividend Payout Ratio to the change of stock price on the manufacturing companies which are listed in Indonesia Stock Exchange.The samples have been selected by using purposive sampling technique to the 36 manufacturing companies which have published their financial statements in 2011-2013 periods. Therefore, 108 financial statements which meet the sample criteria have been obtained.The analysis technique has been done by using multiple regressions analysis and the independent variables i.e.: Working Capital to Total Assets (WC/TA), Retained Earnings to Total Assets (RE/TA), Sales to Total Assets (S/TA), Earnings before Interests and Tax to Total Assets (EBIT/TA), Market Value of Equity to Book Value of Total Liabilities (MVE/BTL), Dividend Payout Ratio (DPR) and the dependent variable i.e.: the change of stock price.The result of the research has found that Working Capital to Total Assets (WC/TA), Earnings Before Interest and Tax to Total Assets (EBIT/TA) and Dividend Payout Ratio (DPR) variables have influence to the change of stock price, whereas the Retained Earnings to Total Assets (RE/TA), Sales to Total Assets (S/TA), Market Value of Equity to Book Value of Total Liabilities (MVE/BTL) variables do not have any significant influence to the stock price and simultaneously Working Capital to Total Assets (WC/TA), Retained Earnings to Total Assets (RE/TA), Sales to Total Assets (S/TA), Earnings before Interests and Tax to Total Assets (EBIT/TA),Market Value of Equity to Book Value of Total Liabilities (MVE/BTL) and Dividend Payout Ratio (DPR) variables have significant influence to the change of stock price.Keywords: Financial Distress, DPR, and Change of Stock Price.